How accurate are palliative care doctors at recognising dying?. Issue 3 (1st September 2016) - White, Nicola; Harris, Adam; Reid, Fiona; Harries, Priscilla; Minton, Ollie; McGowan, Catherine; Lodge, Philip; Tookman, Adrian; Stone, Patrick
Abstract : Background: Before being able to plan for end of life care, a doctor must first recognise that a patient is dying. A recent review has highlighted that doctors are not very good at this (Neuberger, 2013). Aim: We set out to develop a "test" to assess how accurate doctors are at recognising dying. The test will consist of case studies, or "vignettes", based on real palliative care patients. Methods: In order to create the vignettes for the test, we undertook a prospective observational study of patients at two sites (a hospice and a hospital palliative care team). Any inpatient, over 18 years old, English speaking, and who was identified by the palliative care team as likely to die within the next two weeks was eligible. The clinical course of each patient was observed and was used to create a vignette, which formed the basis of the prognostic test. Results: 50 participants were recruited and 20 were used to devise a prognostic test. For each vignette, clinicians were asked to assess the likelihood of death in the next 72 hours (scale 0% to 100%) based on the information presented. Illustrative examples of the test questions will be presented at the conference. Conclusions: We have developed a standardised test to assess clinicians' abilities to accurately diagnose imminent death. This test may be used to identify doctors who are most accurate at recognising dying. This may lead to an improved understanding of how this clinical skill is acquired and how it can be taught to less expert clinicians. Reference: Neuberger J. More care, less pathway: a review of the Liverpool Care Pathway; 2013. Available at: https://www.gov.uk/government/uploads/system/uploads/attachment_data/file/212450/Liverpool_Care_Pathway.pdf